(untitled) (PerCursos, 2024)
This article discusses the results of the analysis of the dimensions of the textual experience of Escrevivência in Conceição Evaristo’s body of work, comparing its presence in the productions of different Black researchers from the first class that entered a graduate program in Education at a university in the southern region of Brazil by the affirmative action policy. The Evaristian textual experience is deeply marked by the experiences and corporeality of Black women. It blends writing with life, relating themes such as Afro-Brazilian religiosity and ancestry. Incorporated into educational research, Escrevivência is a different way of questioning reality and experiencing intellectuality, based on a sense of Black belonging capable of claiming the right to difference in writing and academic practices. Escrevivência, understood as a germinating word rather than a concept, configures what is traditionally called a method or methodology in the studies analyzed. Based on the analysis of academic productions, it is argued that Escrevivência is a living word that has a trajectory and germinates research practices and forms of writing in which authorship is the result of shared Black experience and knowledge inherited from traditional communities.